1993
DOI: 10.1152/ajplung.1993.265.5.l421
|View full text |Cite
|
Sign up to set email alerts
|

Radioligand binding methods: practical guide and tips

Abstract: Radioligand binding assays are a relatively simple but extremely powerful tool for studying receptors. They allow an analysis of the interactions of hormones, neurotransmitters, growth factors, and related drugs with the receptors, studies of receptor interactions with second messenger systems, and characterization of regulatory changes in receptor number, subcellular distribution, and physiological function. As a result, these assays are widely used (and often misused) by investigators in a variety of discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 0 publications
1
94
0
Order By: Relevance
“…3B) indicated that, in addition to G h /fXIIIA and S171E, K173L and K173N were impaired in GTP binding. This is informative, because in our hands, WT G h has an affinity for GTP of ϳ25 nM, 2 and affinities lower than this cannot be readily detected by filtration assays (28). Thus, the lack of GTP␥S binding by K173L and K173N, both of which photolabel, indicates that these two mutants have a lower affinity for GTP than WT.…”
Section: Isolation and Sequence Analysis Of Gtp-binding G H Pep-mentioning
confidence: 79%
“…3B) indicated that, in addition to G h /fXIIIA and S171E, K173L and K173N were impaired in GTP binding. This is informative, because in our hands, WT G h has an affinity for GTP of ϳ25 nM, 2 and affinities lower than this cannot be readily detected by filtration assays (28). Thus, the lack of GTP␥S binding by K173L and K173N, both of which photolabel, indicates that these two mutants have a lower affinity for GTP than WT.…”
Section: Isolation and Sequence Analysis Of Gtp-binding G H Pep-mentioning
confidence: 79%
“…␣-1L ARs could not be detected in the membrane preparations, even though the binding conditions were identical to those used for the intact tissue segment binding procedures. The classical radioligand binding assay using microsomal membrane preparations eliminates some nonspecific binding (Bylund and Toews, 1993;Mackenzie et al, 2000) but may result in a loss of receptors upon homogenization and fractionation . This type of loss of receptor upon homogenization has been suggested to be especially important for small tissues (Colucci et al, 1981;Faber et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, a selective loss of ␣-1L AR, in contrast with the ␣-1A AR, cannot be ruled out. Since tissue homogenization changes receptor environment, binding to receptors in membrane preparations may not reflect the binding to receptors present in intact cells (Bylund and Toews, 1993). It is possible that a selective loss of the ␣-1L AR binding phenotype is related to a conformational modification or the environmental changes caused by homogenization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low value of this linearity of curve ( r ) is might be due to less optimal separation of bound radioligand from free radioligand. The separation is crucial step in RBA method, it is important to prevent dissociation of the receptor-radioligand complex which this parameter is measured [17]. The value of Kd and Bmax was obtained from this equation i.e Kd = -(1/slope) = -(1/-0.038) = 26.316 nM and Bmax = intercept = 9.302 nM.…”
mentioning
confidence: 99%